Evaluation of the Anti-inflammatory Activity of Equisetum arvense and Baccharis trimera Fractions - Vaz, Carolina Ferreira; Mariano, Alan Fernandes; Fracasso, Júlia Amanda Rodrigues; Ramos, Marcus Vinicius Vieitas; Santos, Lucineia dos; Dias, Herbert Júnior (Archives of Pharmacy and Pharmaceutical Sciences, 2024)
Inflammation is a natural response of the body to defend itself against potential threats and can be reduced through physical activity, proper nutrition, and the use of herbal medicines, which are medicinal plants. In the study, we aim to examine the anti-inflammatory effects of the volatile and ethanolic fractions of two commonly used medicinal plants, Equisetum arvense, and Baccharis trimera. The essential oils were obtained by hydrodistillation of the fresh leaves of the plants, while the ethanolic extracts were obtained using classical methodologies. All fractions were tested for anti-inflammatory activity, evaluating their ability to stabilize the red blood cell membrane and inhibit the spreading, and phagocytosis by macrophages, at concentrations varying from 200 to 600 µg mL-1. The results of the experiments suggest that the ethanolic fraction of B. trimera shows promising results compared to the positive controls. Our investigations thus contribute to the specialized literature on the use of herbal medicines around nutrition, providing guidance for future studies on these fractions.